The dietary inflammatory index and asthma prevalence: a cross-sectional analysis from NHANES - Lu, Chuansen; Zhu, Yike (Frontiers in Nutrition, 2024)
Background: Inflammation is a key factor in the development of asthma, and diet significantly influences inflammatory responses. This study examines the relationship between the Dietary Inflammatory Index (DII) and asthma prevalence.We conducted a cross-sectional analysis using data from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. Demographic details, anthropometric measurements, dietary habits, lifestyle factors, and asthma status were recorded for all participants. Multivariable logistic regression was utilized to assess the link relationship between DII and asthma prevalence. Additionally, restricted cubic spline (RCS) analysis was employed to explore the nonlinearity and dose-response relationship between the DII and asthma risk. Subgroup analyses were stratified by gender, age, race, body mass index (BMI), poverty income ratio (PIR), education, smoking status, alcohol use, and family medical history were performed to dissect the association of the between DII and asthma across diverse populations.The analysis included 37,283 adults from NHANES. After adjusting for potential confounders in the multivariable logistic regression model, a significant positive association was identified between DII and asthma (OR, 95% CI: 1.05, 1.02-1.09, per 1 SD increase). The RCS analysis revealed a nonlinear association (P for nonlinearity = 0.0026), with an inflection point at 1.366, beyond which an increase in DII was significantly correlated associated with asthma risk. Furthermore, the stratified analyses indicated a positive correlation association between DII and asthma in the majority of subgroups.The findings underscore a significant and nonlinear association between DII and asthma. To enhance asthma prevention and management, greater emphasis should be placed on modulating dietary-induced inflammation.